Development and Initial Validation of the Pediatric Neuromuscular Recovery Scale. Issue 4 (2016) - Ardolino, Elizabeth M.; Mulcahey, Mary Jane; Trimble, Shelley; Argetsinger, Laura; Bienkowski, Marci; Mullen, Courtney; Behrman, Andrea L.
Abstract : The purpose of this study was to develop and complete the initial validation of a pediatric version of the Neuromuscular Recovery Scale. Abstract : Purpose: The Neuromuscular Recovery Scale (NRS) was developed to assess the capacity of adults' post-spinal cord injury (SCI) to perform functional tasks without compensation. Application of the NRS to children has been challenging. The purpose of this study was to develop and complete the initial validation of a pediatric version of the NRS. Methods: First, the investigative team developed a draft Pediatric NRS. Next, a Delphi method was used to amend the draft by 12 pediatric experts. Finally, the revised Pediatric NRS was field-tested on a sample of children with SCI (n = 5) and without (n = 7). Results: After the Delphi process and field testing, the Pediatric NRS consists of 13 items scored on a 12-point scale. All items, except 1, achieved 80% agreement by experts. Conclusions: This is the first step in development and validation of a pediatric SCI scale that evaluates neuromuscular capacity, in the context of pediatric function, without compensation.